2016
DOI: 10.1186/s13054-016-1482-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma growth-differentiation factor-15 for prediction of acute kidney injury in patients undergoing cardiac surgery

Abstract: BackgroundGrowth-differentiation factor-15 (GDF-15) is an emerging humoral marker for risk stratification in cardiovascular disease. Cardiac-surgery-associated acute kidney injury (CSA-AKI), an important complication in patients undergoing cardiac surgery, is associated with poor prognosis. The present secondary analysis of an observational cohort study aimed to determine the role of GDF-15 in predicting CSA-AKI compared with the Cleveland-Clinic Acute Renal Failure (CC-ARF) score and a logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Geoge J et al [3] analyzed 586 patients who undergoing elective aortic hemiarch reconstruction, they also found CPB time (min) (OR = 1.01, 95% CI: 1.00–1.01; P = 0.03) was an independent risk factor of postoperative AKI. Moreover, several other studies [5, 13, 18, 23, 30] had found that CPB time was an independent predictor of postoperative AKI in patients underwent cardiac and vascular surgery which further verified our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Geoge J et al [3] analyzed 586 patients who undergoing elective aortic hemiarch reconstruction, they also found CPB time (min) (OR = 1.01, 95% CI: 1.00–1.01; P = 0.03) was an independent risk factor of postoperative AKI. Moreover, several other studies [5, 13, 18, 23, 30] had found that CPB time was an independent predictor of postoperative AKI in patients underwent cardiac and vascular surgery which further verified our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Actually, pre-operation elevated sCr concentration might also indicate structural kidney damage or hemodynamic derangements in acute aortic dissection patients, which further aggravated the development of postoperation AKI and the requirement of CRRT. Previous reports also showed the CPB time is an independent risk factor for postoperative AKI during routine cardiac surgery [14,15]. Specifically for aortic surgery, Roh GU et al [1] analyzed 98 patients who underwent graft replacement of the thoracic aorta and found that longer CPB time (> 180 minutes; OR, 7.50; P = 0.008) were independent risk factors for postoperative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify high-risk subjects in the early stages to prevent CIN. In the previous study, the incidence of postoperative acute kidney injury increased in patients with high level of preoperative plasma GDF-15, indicating that GDF-15 is useful for risk stratification of CIN in patients with normal creatinine[ 19 , 20 ]. Our study further explored the associations between GDF-15 level and CIN in AMI patients underwent PCI.…”
Section: Discussionmentioning
confidence: 99%